Augmenting Decision-Making Skills: Essential in Leading to the Up-Gradation of Living Conditions - Dr. Radhika Kapur, (Indian Journal of Management and Language (IJML), 2025)
Throughout the lives of individuals, in both personal and professional spheres, they are required to make wise and productive decisions regarding various subjects and concepts. Family members make decisions for their children, but when one reaches the adulthood stage, they can make their own decisions. This is regarded as an integral part of individuals' lives. The upgradation of analytical and critical-thinking skills is viewed as vital in making wise and productive decisions in various areas. Furthermore, individuals need to ensure that decisions are flexible. In other words, changes can be implemented in a manner that effectively influences the decisions made. The decisions made need to be favourable to individuals in bringing about improvements in their overall quality of life. Within all types of organizations, individuals in leadership positions are vested with the authority and responsibility of making wise and productive decisions. Furthermore, they ensure that the decisions made facilitate an increase in employee morale and lead to improvements in the overall organisational structure. Hence, within personal and professional lives, the honing of decisionmaking skills facilitates the promotion of well-being and goodwill. Therefore, it is understood that augmenting decisionmaking skills is essential for improving living conditions. The main concepts considered in this research paper are understanding the meaning and significance of augmenting decision-making skills, measures to be implemented for augmenting decision-making skills, and the advantages of augmenting decision-making skills.